The cysteine, total sulfur amino acid, tyrosine, phenylalanine plus tyrosine, and non-essential amino acid maintenance requirements of broiler breeders - Ekmay, R. D.; Mei, S. J.; Sakomura, N. K. [UNESP]; Coon, C. N. (Oxford Univ Press, 2016)
Two hundred and fifty Cobb-Vantress broiler breeders were used to determine the maintenance requirement and efficiency of utilization of dietary Cys, Tyr, and non-essential amino acids (AA) in a 21-day experiment. The breeders were fed crystalline amino acid diets containing graded levels of Cys or Tyr representing 0, 10, 20, 30, and 40% of their suggested requirement level with all other amino acids maintained at 40% of their suggested requirement level. To determine the non-essential AA maintenance requirement, graded levels of non-essential AA were provided by glutamic acid to represent 12, 19, 26, 33, and 40% of the ideal level of glutamic acid with all other amino acids maintained at their maintenance requirement level. The total sulfur amino acid (TSAA) and Phe + Tyr requirements were calculated by combining Cys and Tyr results, respectively, with previously determined Met and Phe, respectively. The slope of Cys, Tyr, and non-essential AA accretion regression line indicated that 29% Cys, 24% TSAA, 21% Tyr, 20% Phe + Tyr, and 9% nonessential AA of crystalline amino acids were retained. The Cys requirement for zero protein accretion was calculated to be 30.48 mg/d or 17.006 mg/kgBW(0.75)/d or 75.426 mg/kgCP/d. The TSAA requirement for zero accretion was calculated to be 132.25 mg/b/d, 71.48 mg/kgBW(0.75)/d, and 307.55 mg/kgCP/d. The Tyr requirement for zero protein accretion was calculated to be 65.907 mg/d or 37.233 mg/kgBW(0.75)/d or 175.566 mg/kgCP/d. The Phe + Tyr requirement for zero protein accretion was calculated to be 352.18 mg/b/d, 190.37 mg/kgBW(0.75)/d, and 749.33 mg/kgCP/d. The non-essential AA requirement for zero protein accretion was calculated to be 3715.194 mg/d or 2003.155 mg/kgBW(0.75)/d or 9452.954 mg/kgCP/d.
Keywords: broiler breeders; TSAA; Phe plus Tyr; non-essential amino acids; maintenance